Book Review, Military Legal Proceedings in Malaysia: Teo Say Eng & Colonel Wan Nor Mazlan (2009), LexisNexis(HardCover) - Ab Aziz, Shamrahayu (LexisNexis, 2010)
The book Military Legal Proceedings in Malaysia which was launched by the Minister of Defence in Kuala Lumpur last year is among the pioneer publications on the Malaysian military legal proceeding though it is not the first publication on the subject. Way back in 1984, P Suppiah penned Malaysian Military Law 2 in which some aspects in military legal proceedings were mentioned. A review of the book was published in 1985. 3 The 167 pages P Suppiah Malaysian Military Law provides a brief discussion on military law and military legal proceedings in Malaysia. It provides guide for those directly involved in courts-martial proceedings such as the defence counsel and the courts' officers, including the judges of the courts-martial. 4 However, it was suggested in the book review that few matters regarding substance and technical parts of the book should be improved to make it more informative and useful. 5